Proceedings of the 2006 AVI Workshop on BEyond Time and Errors: Novel Evaluation Methods for Information Visualization 2006
DOI: 10.1145/1168149.1168162
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics for information visualization evaluation

Abstract: Heuristic evaluation is a well known discount evaluation technique in human-computer interaction (HCI) but has not been utilized in information visualization (InfoVis) to the same extent. While several sets of heuristics have been used or proposed for InfoVis, it is not yet known what kind of heuristics are useful for finding general InfoVis problems. We performed a meta-analysis with the goal of exploring the issues of heuristic evaluation for InfoVis. This meta-analysis concentrates on issues pertaining to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 19 publications
(27 reference statements)
0
68
0
3
Order By: Relevance
“…The visualization literature contains a multitude of proposed methods for evaluating visualization tools in the wild [13,33,69,85,95], as well as guidance on using them [39,50]. The most common form of validation are case studies with real users, real problems, and real data, as featured in many strong design studies by others [35,58], and many of our own [10,40,43,44,45,46,71,74,76,77].…”
Section: Deploy: Release and Gather Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…The visualization literature contains a multitude of proposed methods for evaluating visualization tools in the wild [13,33,69,85,95], as well as guidance on using them [39,50]. The most common form of validation are case studies with real users, real problems, and real data, as featured in many strong design studies by others [35,58], and many of our own [10,40,43,44,45,46,71,74,76,77].…”
Section: Deploy: Release and Gather Feedbackmentioning
confidence: 99%
“…The relevant literature instead focuses on methods for designing [1,42,66,79,82,90,91] and evaluating [13,33,39,50,68,69,76,80,85,86,95] visualization tools. We distinguish between methods and methodology with the analogy of cooking; methods are like ingredients, whereas methodology is like a recipe.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have proposed the use of inspection methods as part of their evaluation methodology for information visualization systems [23,25,34,35,38]. In general, there are two styles of inspection method: those that are based on a set of design guidelines, such as heuristic evaluations; and those that are based on performing specific tasks, such as cognitive walkthroughs.…”
Section: Inspection Methodsmentioning
confidence: 99%
“…Both Freitas et al [8] and Zuk et al [38] have suggested that inspection methods can be extended to include the consideration of specific issues relevant to information visualization. Their extensions include evaluating the codification of information, the completeness of the information being visually represented, and the spatial organization of the objects in the visual display.…”
Section: Inspection Methodsmentioning
confidence: 99%
“…Os procedimentos metodológicos adotados buscam: analisar e resumir as principais ideias relacionadas a "experiência na educação", contidas na obra de John Dewey (2010;2011a;2011b); analisar e resumir as principais ideias relacionadas ao "processo de individuação", contidas na obra de Gilbert Simondon (2007;2009;2012;; propor aproximações e contraposições entre a categoria "meio comum" (homem, processo cognitivo, máquina e situação), a categoria "código e informação" (ruído, regularidade e acaso), a categoria "experiência e/ou individuação" (interação, continuidade, confronto e eleição) e a categoria "aprendizado, invenção e/ou significação" (percepção, análise, síntese, sincronia e revelação); propor parâmetros capazes de contribuir com a concepção e a elaboração de um "modelo de visualização de dados" sobre a história do design (Carpendale, 2013;Carusi, 2010;Drucker, 2011;Zuk, 2006a;Zuk, 2006b); e finalmente, formalizar a análise e a descrição dos resultados teóricos obtidos na pesquisa.…”
Section: Metodologiaunclassified